DAMPAK LEVERAGE DAN DEWAN KOMISARIS TERHADAP NILAI PERUSAHAAN - Pramita Indraswari, I G A A; Budiadnyani, Ni Putu; R. Aprilyani Dewi, Putu Pande (LPPM Universitas Bina Bangsa, 2025)
Firm value is an important measure of a company's performance and success. Firm value includes various factors, including the company's financial condition, market position, growth potential, and the value perceived by investors and stakeholders. This study aims to examine whether there is an effect of leverage and the board of commissioners on firm value. The population in this study were all food and beverage companies listed on the Indonesia Stock Exchange, as many as 26 food and beverage companies. The sampling technique used was purposive sampling. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses multiple linear regression analysis with SPSS. The results of this study provide empirical evidence that partially the leverage variable and the board of commissioners have a positive effect on firm value.